Distributed Digital Preservation in the Cloud - David S. H. Rosenthal; Daniel L. Vargas (International Journal of Digital Curation, 2013)
The LOCKSS system is a leading technology in the field of Distributed Digital Preservation. Libraries run LOCKSS boxes to collect and preserve content published on the Web in PC servers with local disk storage. They form nodes in a network that continually audits their content and repairs any damage. Libraries wondered whether they could use cloud storage for their LOCKSS boxes instead of local disks. We review the possible configurations, evaluate their technical feasibility, assess their economic feasibility, report on an experiment in which we ran a production LOCKSS box in Amazon’s cloud service, and describe some simulations of future costs of cloud and local storage. We conclude that current cloud storage services are not cost-competitive with local hardware for long term storage, including for LOCKSS boxes.